Not All Selfies Took Alike: Distinct Selfie Motivations Are Related to Different Personality Characteristics - Etgar, Shir; Amichai-Hamburger, Yair (Frontiers in Psychology, 2017)
Selfies have become a frequent and commonplace occurrence, though the reasons which lead people to take selfies remain unclear. This research explores what motivates selfie taking, and suggests that this is not a uniform phenomenon and varying motivations may be found among selfie takers. In addition, the connection between these distinct selfie motivations and personality characteristics, including the big five, narcissism, and self-esteem, as well as types of selfie behaviors are examined. At the first stage of the research, 117 participants filled out a questionnaire dealing with their reasons for taking selfies. An explanatory factor analysis revealed three distinct selfie motivations: self-approval, belonging, and documentation. At the second stage, 191 different participants answered both the same questionnaire, and personality traits questionnaires. A confirmatory factor analysis verified that the three selfie motivations model has a good fit. Our results suggested that each selfie motivator is differently related to personality characteristics: self-approval was negatively related to: conscientiousness, emotional stability, openness to experiences, and self-esteem, and positively correlated to frequent checking for “likes.” Belonging was related to openness to experiences. Documentation was related to agreeableness and extroversion. Unlike previous studies, none of the selfie motivating factors was found to relate to narcissism. The reasons for these differences, as well as the need to refer to selfie taking as a multidimensional phenomenon, are discussed.